2003
DOI: 10.1111/j.1365-2869.2003.00363.x
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative similarities in cognitive impairment associated with 24 h of sustained wakefulness and a blood alcohol concentration of 0.05%

Abstract: SUMMAR Y Previous studies that have quantified fatigue-related cognitive impairment as blood alcohol concentration (BAC) equivalents have been limited by two issues: the effect of practice on tests of cognition and, more importantly, the statistic used to quantify change in cognitive performance. The current study addressed these issues by adopting an ABACA design, which allowed for the adequate control of practice effects, and by using effect size metrics, which enabled direct comparisons to be made in perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 130 publications
(96 citation statements)
references
References 37 publications
3
92
0
1
Order By: Relevance
“…CogHealth TM has been previously used to document cognitive impairment due to sleep deprivation or alcohol intake in young adults [Falleti et al, 2003] and to measure improvements in cognitive performance among normal children between 8 and 12 years of age [Mollica et al, 2005]. The Stroop test has also been successfully used in children of this age [Shum et al, 2008].…”
Section: Discussionmentioning
confidence: 99%
“…CogHealth TM has been previously used to document cognitive impairment due to sleep deprivation or alcohol intake in young adults [Falleti et al, 2003] and to measure improvements in cognitive performance among normal children between 8 and 12 years of age [Mollica et al, 2005]. The Stroop test has also been successfully used in children of this age [Shum et al, 2008].…”
Section: Discussionmentioning
confidence: 99%
“…Similar figures have been estimated in Australia 15) and the UK 18) . Finally, research has also indicated that the performance decrements associated with sleep deprivation can be equated to those of alcohol [19][20][21] . Therefore, a strong case can be made from a public safety perspective that driving whilst fatigued should be an offence.…”
Section: Prosecution Decisionmentioning
confidence: 99%
“…3 Indeed, many studies find evidence for an inverse relationship and link sleep insufficiencies to decreased attention and cognitive performance (Dijk et al, 1992;Beaumont et al, 2001;Caldwell et al, 2004;Falleti et al, 2003;Smith et al, 2002). Graeber (1994) provides evidence that sleep insufficiencies and disruptions of the circadian rhythm negatively affect cognitive functioning.…”
Section: Dst Mechanismsmentioning
confidence: 99%